Chemical Properties of Groundwater in Bhiloda Taluka Region, North Gujarat, India - G. D. Acharya; M. V. Hathi; Asha D. Patel; K. C. Parmar (E-Journal of Chemistry)
Groundwater is one of the most useful water sources. Contamination of such water source is a big problem creating health hazards. In this present study we have collected groundwater samples from different places of Bhiloda taluka of Sabarkantha district (North Gujarat) India. These samples have been assessed on the basis of various qualitative parameters. The results of physico-chemical study of water samples from 13 bore wells in Bhiloda taluka are presented. The water quality parameters such as; pH, electrical conductivity (EC), total dissolved salts (TDS), calcium and magnesium, sodium, potassium, carbonate, bicarbonate, chloride, sulphate, fluoride, sodium adsorption ratio (SAR), residual sodium carbonate (RSC) and soluble sodium percentage ( SSP ) were estimated.